From Mesenchymal Stromal/Stem Cells to Insulin-Producing Cells: Immunological Considerations - Refaie, Ayman F.; Elbassiouny, Batoul L.; Kloc, Malgorzata; Sabek, Omaima M.; Khater, Sherry M.; Ismail, Amani M.; Mohamed, Rania H.; Ghoneim, Mohamed A. (Frontiers in Immunology, 2021)
Mesenchymal stem cell (MSC)-based therapy for type 1 diabetes mellitus (T1DM) has been the subject matter of many studies over the past few decades. The wide availability, negligible teratogenic risks and differentiation potential of MSCs promise a therapeutic alternative to traditional exogenous insulin injections or pancreatic transplantation. However, conflicting arguments have been reported regarding the immunological profile of MSCs. While some studies support their immune-privileged, immunomodulatory status and successful use in the treatment of several immune-mediated diseases, others maintain that allogeneic MSCs trigger immune responses, especially following differentiation or in vivo transplantation. In this review, the intricate mechanisms by which MSCs exert their immunomodulatory functions and the influencing variables are critically addressed. Furthermore, proposed avenues to enhance these effects, including cytokine pretreatment, coadministration of mTOR inhibitors, the use of Tregs and gene manipulation, are presented. As an alternative, the selection of high-benefit, low-risk donors based on HLA matching, PD-L1 expression and the absence of donor-specific antibodies (DSAs) are also discussed. Finally, the necessity for the transplantation of human MSC (hMSC)-derived insulin-producing cells (IPCs) into humanized mice is highlighted since this strategy may provide further insights into future clinical applications.